Neural cell models for disease modeling and drug discovery - Terrasso, Ana Paula Barreto (2020)
"Neurological disorders are a major public health problem and are expected to rise dramatically together with the higher life expectancy and the shift towards an ageing society. Current therapeutic options can only ameliorate some of the symptoms and there are no effective treatments to target pathological mechanisms and stop disease progression. The human brain complexity hampers the understanding of the brain functioning at the molecular, cellular, and pathophysiological levels for many neurological disorders. This highlights the need for new brain models, which can contribute to unveil molecular mechanisms of neurological disorders, identify therapeutic targets and evaluate preclinically new therapies in a more adequate and predictive basis, withstanding its successful translation to the clinics. Despite their undeniable value, traditional animal models diverge from humans at biochemical and genetic levels. Moreover, 2D in vitro cell-based models do not mimic important aspects of brain cellular heterogeneity, architecture and microenvironment (...)".